PENGEMBANGAN MEDIA PEMBELAJARAN SMART BOARDGAME BERBASIS STIFIN LEARNING DALAM MENCIPTAKAN PEMBELAJARAN EFEKTIF - Ayu, Lestari Ratu; Saman, Abdul; Musi, Muhammad Akil; Zainuddin, M. Said (Universitas Borneo Tarakan, 2023)
This study applies research and development (RD) with ADDIE model. The objects of this research are four students representing four characters of STIFIn concept which aim is to study the need of learning media, the learning media itself, and to find out the validity, practicality, and effectiveness of STIFIn-Learning-Concept-Based Smartboard Game learning media in creating effective learning at Nurul Ummu Kindergarten. After analyzing, the result of this study shows that the need of a smartboard game learning media obtained 3,33 score with the category of very valid, and the description of the learning media itself is in the layout model of user’s guideline book. The description of the validity, practicality, and effectiveness were validated by two expert validators. In the validation of the guidebook, the researcher obtained 3,36 score with the category of very valid. The result is different from the teachers’ response where 3,14 is gained with the category of valid. Another score of 3,31 is obtained in the validity of learning media evaluation with the category of very valid. In the analysis of practicality measured with teachers’ response questionnaires, the researcher got 92,78% with the category of totally agree. Whereas in the analysis of effectiveness measured with the result of media evaluation by teachers, the score of 85,83% is obtained with the category of effective when applied in early childhood learning. This concludes that the need of STIFIn-Learning-Concept-Based Smartboard Game learning media is very much needed in the process of learning. In addition, the users’ guidebook is considered valid, practical, and effective when applied in the early childhood learning